NILAI-NILAI SUBSTANSIAL DALAM MACAPAT Substansial Values of The Sekar Macapat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Sekar Macapat is one kind of traditional Javanese poems which is used by poets to express their works. The purpose of this research is twofold. First, it is to systematize the ethics of the Sekar Macapat. It is expected that the systemization can formulate psichological values of kindness which enables to be a bases for human behavior. Second, it is top place ethical values of Sekar Macapat in the body of ethical theories in general. It is a library research, in which the data were analyzed and interpreted by means of descriptive, analitical (critical), and idealistic method. The descriptive method is used to reveal the substantial values of Sekar Macapat. The analysis method is used to find out the relationship and the similarity of concepts of the Sekar Macapat, while the idealistic method is used to construct the ethical concept of the Sekar Macapat. The data were collected from the works of Sri Mangkunegara IV and other author of Sekar Macapat. The result of the data analysis shows highly substantial values of the Sekar Macapat. They are moral values that are mentally and spiritually useful for human kinds. Since the moral values are based on high values, they are expected to bring about a better life. The high values can be used to socialize human values in accordance with the second principle of Pancasila (the live principles), that is just and civilized humanity. Sekar Macapat contains educative values that are useful for life. The values will guide human kinds to behave in a good manner in order to achieve an ideal man, i.e. possessing such characters as low profile, well-behavior, wisdom, and courtesy. The moral norms containing high values in the Sekar Macapat is counted as the Eudemonism. Keywords: Sekar Macapat â Javanese poem